2012
DOI: 10.3354/esr00467
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characterisation of bycatch mitigation pingers on shark control nets in Queensland, Australia

Abstract: The Queensland Shark Control Program (QSCP) uses pingers to prevent marine mammal entanglement in shark control nets along public beaches, in Queensland, Australia. Acoustic emissions of Fumunda F3 (designed for humpback whales) and F10 pingers (designed for dolphins) were measured and characterised. The acoustic signals consisted of tones (3 and 10 kHz, respectively) and harmonic overtones emitted for about 400 ms every 5 to 6 s. Directivity was more pronounced for the overtones. Broadband source levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…This 5 m depth is similar to that used by Erbe & McPherson (2012) in their modelling of acoustic characteristics of these whale alarms. Previous research undertaken at Cape Solander suggested that about 90% of migrating humpback whales should pass between 1.5 and 10 km of the coast.…”
Section: Whale Alarmmentioning
confidence: 54%
See 2 more Smart Citations
“…This 5 m depth is similar to that used by Erbe & McPherson (2012) in their modelling of acoustic characteristics of these whale alarms. Previous research undertaken at Cape Solander suggested that about 90% of migrating humpback whales should pass between 1.5 and 10 km of the coast.…”
Section: Whale Alarmmentioning
confidence: 54%
“…whale calls, snapping shrimp) and abiotic sounds (e.g. wind, waves, rain) (Nystuen & Farmer 1987, Erbe & McPherson 2012 as well as anthropogenic noise (e.g. shipping noise, underwater construction; McCarthy & Miller 2002, Hildebrand 2009 needs to be taken into account when deploying acoustic alarms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic sources include seismic exploration (Erbe and King, 2009;Greene and Richardson, 1988), pile driving (Erbe, 2009), dredging (Reine et al, 2014), petroleum production operations (Erbe et al, 2013;Wyatt, 2008), equipment such as sonars, echosounders, acoustic tags and pingers (Ainslie, 2010;Erbe and McPherson, 2012), explosions (Soloway and Dahl, 2014), as well as ships of all sizes (Erbe, 2002(Erbe, , 2013aRoss, 1976;Scrimger and Heitmeyer, 1991). Propeller cavitation is typically the strongest source of ship noise from large vessels and exhibits a broadband spectrum, amplitude modulated at the propeller blade rate (i.e.…”
Section: Anthrophonymentioning
confidence: 99%
“…One such technology is acoustic alarms known as "pingers". These devices can be to attached to fishing gear and emit a tone underwater within the hearing range of target marine mammals [12] . The devices serve to "illuminate" the gear with sound and warn the animals of its presence to encourage them to avoid it.…”
Section: Introductionmentioning
confidence: 99%